Establishment of residential flood damage function model for Kuantan, Malaysia - Noor Suraya, Romali; Zulkifli, Yusop (2019)
Flood damage estimation is an essential element in the assessment of flood risk. However, the study on flood damage in developing countries is limited due to the scarcity of historical data